Evaluation of the effect of drinking alcohol on interleukin-6 Statistical study - Ali Hussein, Muthanna (International Journal of Psychosocial Rehabilitation, 2020)
Background: Drinking alcohol has adverse effects on the control of allergic sensitization and bronchitis. Also, numerous studies related to IL-6 have revealed a huge amount of information on the different roles for this cytokine in homeostatic regulation and disease pathogenesis.Methods: 100 is the total number of subjects who participated in our study and were suffering from bronchitis; 50 of them were drinking alcohol, and the other 50 subjects were non-drinking alcohol as controls. Our study lasted for four months Between November 2020 and the end of February 2021, I drank alcohol, consuming 100-300 ml a day regularly for at least five years. Also, drinking alcohol has given me respiratory allergies. The ethical guidelines acceptance form was taken and signed by each volunteer Blood samples were collected via GEL & Clot Activator-5 ml blood tubes to separate the IL-6 serum